2020
DOI: 10.1038/s41598-020-78004-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential clusterization of soluble and extracellular vesicle-associated cytokines in myocardial infarction

Abstract: A proinflammatory dysregulation of cytokine release is associated with various diseases, in particular with those of infectious etiology, as well as with cardiovascular diseases (CVD). We showed earlier that cytokines are released in two forms, soluble and in association with extracellular vesicles (EVs). Here, we investigated the patterns of expression and clustering of soluble and EV-associated cytokines in patients with ST-elevation myocardial infarction (STEMI). We collected plasma samples from 48 voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
(155 reference statements)
3
2
0
Order By: Relevance
“…Previous evidence, similar to our results, has described an increase in circulating IP-10 in patients with acute myocardial infarction associated with the size of the infarct [32]; other investigations have not found a change in TNF-α between healthy subjects and patients, similar to our results [20]. Consistent with our results, another study demonstrated high concentration levels of IL-1β, IL-6 and IL-12p70 in patients with STEMI [33] and showed that these were associated with a lower improvement response in patients with advanced heart failure [34]. These results indicate a highly inflammatory environment in patients with STEMI, which could favor postinfarction pathogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…Previous evidence, similar to our results, has described an increase in circulating IP-10 in patients with acute myocardial infarction associated with the size of the infarct [32]; other investigations have not found a change in TNF-α between healthy subjects and patients, similar to our results [20]. Consistent with our results, another study demonstrated high concentration levels of IL-1β, IL-6 and IL-12p70 in patients with STEMI [33] and showed that these were associated with a lower improvement response in patients with advanced heart failure [34]. These results indicate a highly inflammatory environment in patients with STEMI, which could favor postinfarction pathogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, EVs have been known to carry or present cytokines on their surface, including TNFα, IL1β, and IL6 [ 35 ]. This aligns with findings in clinical settings, such as in patients with myocardial infarction, where EV-associated cytokines have shown dysregulation [ 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…In agreement, transcriptome data was correlated with an upregulation of regulatory genes involved in inflammatory responses and ECM following post-MI healing (Li et al, 2019) and isoproterenol-induced hypertrophy (Lau et al, 2018). A significant dysregulation of long non-coding RNA was found in cardiac fibroblasts upon pressure overload (Piccoli et al, 2017), while distinctive patterns of circulating soluble cytokines (Lebedeva et al, 2020), EV-enclosed proteins and miRNA (Otero-Ortega et al, 2021) were also identified, corroborating the importance of long-distance intra-cardiac and systemic communication in remodeling of the heart.…”
Section: Intercellular Communication Changes Associated With Myocardial Infarction Hypertrophy and Heart Failuresupporting
confidence: 65%